Game Theory for Networking Applications - Song, Ju Bin.; Li, Husheng; Coupechoux, Marceau; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides recent results of game theory for networking applications. The contributors address the major opportunities and challenges in applying traditional game theory as well as intelligent game theory to the understanding and designing of modern network systems, with emphasis on both new analytical techniques and novel application scenarios. After an overview of game theory for networks, the book narrows in on game theory in communications, game theory in wireless networks, and game theory applications. The book features contributions from researchers and professionals around the world. Presents a variety of perspectives on game theory for networking applications; Shows how game theory can apply to the study of data traffic, new generation networks, and smartgrid; Includes recent results of applied game theory for networks, providing some technical progresses in GAMENETS.
Chapter1: Types of Nodes and Centrality Measures in Networks -- Chapter2: The Time-Consistent Shapley Value for Two-Stage Network Games with Pairwise Interactions -- Chapter3: Routing on a Ring Network -- Chapter4: Performance of Dynamic Secure Routing Game -- Chapter5: Content Sponsoring with Inter-ISP Transit Cost -- Chapter6: Matching Games for 5G Network Paradigms -- Chapter7: Enhanced Design of Stochastic Defense System with Mixed Game Strategies -- Chapter8: Optimal Impulse Control of SIR Epidemics over Scale-Free Networks -- Chapter9: Fault-Tolerant Hotelling Games -- Chapter10: A Social Choice Theoretic Approach for Analyzing User Behavior in Online Streaming Mobile Applications -- Chapter11: Social Coordination and Network Formation with Heterogeneous Constraints -- Chapter12: Stable and Efficient Structures for the Content Production and Consumption in Information Communities -- Chapter13: One-Player Game based Influential Maximization Scheme for Social Cloud Service Networks -- Chapter14: Noncooperative Energy Charging and Discharging Game for Smart Grid -- Chapter15: Stackelberg Differential Game based Charging Control of Electric Vehicles in Smart Grid -- Chapter16: Day-Ahead Demand Management in Multi-Supplier Power Grid under Transmission Constraints.
Keywords: Telecommunication; Game theory; Application software; Electric power production; Communications Engineering, Networks; Game Theory; Computer and Information Systems Applications; Electrical Power Engineering